Intrinsic and Extrinsic Factors Affecting Student Motivation in Completing Thesis - Pranitasari, Diah; Maulana, Irfan (Technium Social Sciences Journal, 2022)
This study aims to determine the intrinsic and extrinsic factors that influence students' motivation to complete their thesis by using self-efficacy variables, the need for achievement, campus environment, and lecturer learning methods to the motivation to complete their thesis at the Indonesian College of Economics. This research method is a questionnaire survey method. The population in this study were morning regular students and evening regular students of the Indonesian College of Economics who graduated in 2019 by 311 people and the study sample was 164 people. The analysis used is SEM- PLS and SmartPLS 3.0 software. The results of this study indicate 3 variables that affect regular morning students: (1) Self-efficacy affects the motivation to complete a thesis of 29.1%. (2) The need for achievement influences the motivation to complete the thesis by 31.9%. (3) Campus environment towards motivation to complete the thesis is 37.5%. And there are 2 variables that affect regular night students: (1) The need for achievement influences the motivation to complete the thesis by 55.5%. (2) The campus environment influences the motivation to complete the thesis by 40.3%.